Biomechanics Potential of the Masseter and Temporal Muscles in the Mandibles of Mesofacial Subjects - Pradebon, Ana Paula Chitolina; Pradebon, Marieli Chitolina; Goulart, Guilherme Reghelin; Jotz, Geraldo Pereira; Malysz, Tais; Páfaro, Júlia Niero; Reis, Magda de Souza; de Campos, Deivis (Journal of Morphological Sciences, 2018)
Introduction The knowledge of the organization of the masseter muscle (MM) and the temporal muscle (TM) is extremely important when related to the study of the stomatognathic system. Moreover, some authors have shown that mastication is of great importance, not only for the intake of food but also for the systemic, mental and physical functions of the body.Materials and Methods We have decided to analyze the biomechanical potential (length of the force arm, muscular work and mechanical advantage) of the MM and TM in the mandibles of mesofacial subjects (n = 34).Results Our results show that the MM exhibits a better biomechanical potential than the TM (p = 0.0001).Conclusion With these data, orthodontists may develop a specific treatment plan and get better results, especially in cases of patients in whom the biomechanical pattern of the temporomandibular joint is unfavorable.
Keywords: masseter muscle; temporal muscle; mesofacial; mandibles